MRI-Derived 3-D-Printed Breast Phantom for Microwave Breast Imaging Validation - Burfeindt, M. J.; Colgan, T. J.; Mays, R. O.; Shea, J. D.; Behdad, N.; Van Veen, B. D.; Hagness, S. C. (IEEE antennas and wireless propagation letters, 2012)
We propose a 3-D-printed breast phantom for use in preclinical experimental microwave imaging studies. The phantom is derived from an MRI of a human subject; thus, it is anthropomorphic, and its interior is very similar to an actual distribution of fibroglandular tissues. Adipose tissue in the breast is represented by the solid plastic (printed) regions of the phantom, while fibro glandular tissue is represented by liquid-filled voids in the plastic. The liquid is chosen to provide a biologically relevant dielectric contrast with the printed plastic. Such a phantom enables validation of microwave imaging techniques. We describe the procedure for generating the 3-D-printed breast phantom and present the measured dielectric properties of the 3-D-printed plastic over the frequency range 0.5-3.5 GHz. We also provide an example of a suitable liquid for filling the fibroglandular voids in the plastic.